Proceedings of the 2019 Federated Conference on Computer Science and Information Systems 2019
DOI: 10.15439/2019f220
|View full text |Cite
|
Sign up to set email alerts
|

Factors that contribute significantly to Scrum adoption

Abstract: Scrum is the most adopted Agile methodology. The research conducted on Scrum adoption is mainly qualitative and there is therefore a need for a quantitative study on Scrum adoption challenges. The primary objective of this paper is to present the findings of a study on the factors that have a significant relationship with Scrum adoption as perceived by Scrum practitioners working within South African organizations. Towards this objective, a narrative review to extract and synthesize the existing challenges was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Ever since the release of the Agile Manifesto in 2001, agile development methods have proven to be beneficial with regards to enhancing ability to handle changing requirements, delivering software more quickly, increasing team productivity, and improving customer satisfaction. [1][2][3][4][5][6] Although they were originally designed for small, single-team projects, success stories have inspired companies to apply them to large-scale endeavors that span over a long period [7][8][9][10][11] and within different contexts. 12 Nevertheless, the original agile methods such as Scrum, XP, or Kanban do not provide guidance on dealing with scaling issues.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since the release of the Agile Manifesto in 2001, agile development methods have proven to be beneficial with regards to enhancing ability to handle changing requirements, delivering software more quickly, increasing team productivity, and improving customer satisfaction. [1][2][3][4][5][6] Although they were originally designed for small, single-team projects, success stories have inspired companies to apply them to large-scale endeavors that span over a long period [7][8][9][10][11] and within different contexts. 12 Nevertheless, the original agile methods such as Scrum, XP, or Kanban do not provide guidance on dealing with scaling issues.…”
Section: Introductionmentioning
confidence: 99%
“…To be able to identify the factors that contribute significantly to the adoption of the Scrum framework, there was a need for testing and evaluation of the CF. This was presented in another paper entitled "Factors that contribute significantly to Scrum adoption" [18] which described the process behind the three iterations of the CF that lead to the factors of significance. During the second iteration of the CF, SACDM was renamed as Scrum Adoption Challenges Conceptual Framework (SACCF).…”
Section: Methodsmentioning
confidence: 99%
“…Factors revealed as significant were the management of the Scrum sprint, and the complexity and relative advantage of the Scrum framework. The details of the analysis results and findings can be obtained from the "Factors that contribute significantly to Scrum adoption" open-access paper [18].…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Hanslo et al conducted [29] study on challenges for adoption of Scrum and carried out factors proposing conceptual framework using a questionnaire survey. They concluded that Scrum is a trending phenomenon of agile approach in South African organizations and recommended that the organizations adopting Scrum in their software development practices, should consider the factors like management of Sprint, complexity and relative advantages.…”
Section: Empirical Analysismentioning
confidence: 99%